RECIPROCAL TEACHING: ONE OF THE METHODS FOR POOR COMPREHENDERS - Umi Yawisah (State Institute for Islamic Studies IAIN of Metro, 2013)
Reciprocal teaching is a method which emphasizes the students’ cognitive and meta cognitive domains for it covers the structural process of the instruction. The whole elements within the procedure enable the students to choose the strategy, plan, monitor, and evaluate their own activities. Furthermore, the procedures integrated in this method are believed to enhance the students’ thinking process. The method, introduced by Palinscar and Brown, belongs to cooperative learning in that the students’ thinking process in learning is expressed through a natural dialogue. This method is designed to improve the students’ competency in text reading while those students find it difficult to comprehend the content of the text. The method also encourages the students to apply such four strategies as predicting, summarizing, questioning, and clarifying.